Biodiversity of Mexican terrestrial arthropods (arachnida and hexapoda): a biogeographical puzzle - Morrone, Juan J.; Márquez, Juan (Instituto de Ecología, A.C., 2008)
We present a general review of the knowledge on Mexican terrestrial arthropods and a set of hypotheses to help explain their biogeographic complexity, translated into biogeographic regions, dominions, provinces, and panbiogeographic nodes. Two biogeographic regions (Nearctic and Neotropical) and one transition zone are recognized. Within them, five dominions (Californian Nearctic, Continental Nearctic, Mexican Mountain, Antillean, and Mesoamerican) and 14 provinces (California, Baja California, Sonora, Mexican Plateau, Tamaulipas, Sierra Madre Occidental, Sierra Madre Oriental, Transmexican Volcanic Belt, Balsas Basin, Sierra Madre del Sur, Yucatán Peninsula, Mexican Gulf, Mexican Pacific Coast, and Chiapas) are recognized. Fifteen geographic areas where three different biogeographic provinces intersect are considered panbiogeographic nodes: California Norte, Sonora, Sonora-Chihuahua-Sinaloa, Jalisco-Nayarit, Jalisco-Zacatecas, Monterrey (Nuevo León), Ciudad Victoria (Tamaulipas), northwestern Michoacán, northern Guerrero, Hidalgo-Puebla, Orizaba-Córdoba (Veracruz), Huajuapan de León (Oaxaca), Sierra de Juárez (Oaxaca), southern Oaxaca, and El Ocote (Chiapas). The Mexican Transition Zone presents the highest level of biotic mixture between Nearctic and Neotropical elements. Species distributed in the lowlands near the Mexican coasts have mostly Neotropical affinities, and can be detected further north than previously hypothesized. Nodes possess a higher biodiversity, with different biogeographic affinities. Some of them are currently under protection for their high biodiversity. None of them has been studied adequately, and future research will be very important to select more sites with high biodiversity, and species representing different lineages and biogeographic histories.